ANALISIS TINGKAT KESIAPAN PENGAMANAN SISTEM INFORMASI - Nurhafifah Matondang; Bayu Hananto; Catur Nugrahaeni (Universitas Negeri Padang, 2019)
The University has a number of data relating to Academic and Higher Education Governance. The large amount of data that requires security, especially in terms of readiness to secure information systems. Maintaining information system security in the university environment aims to maintain confidentiality, fulfill the availability of the system for those who have authority for those who use it and the integrity of the system. The University of National Development